2(3+3x)-7=17

Simple and best practice solution for 2(3+3x)-7=17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3+3x)-7=17 equation:


Simplifying
2(3 + 3x) + -7 = 17
(3 * 2 + 3x * 2) + -7 = 17
(6 + 6x) + -7 = 17

Reorder the terms:
6 + -7 + 6x = 17

Combine like terms: 6 + -7 = -1
-1 + 6x = 17

Solving
-1 + 6x = 17

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 6x = 17 + 1

Combine like terms: -1 + 1 = 0
0 + 6x = 17 + 1
6x = 17 + 1

Combine like terms: 17 + 1 = 18
6x = 18

Divide each side by '6'.
x = 3

Simplifying
x = 3

See similar equations:

| 20x-11-14x=3(2x-5)+4 | | t(t-1)=0 | | 0.5x+5=12.5 | | 4x(4+3y)-9(x+2xy)= | | 5(0.5x+2)=22.5 | | 22.5=10+2.5x | | 35.123/100 | | 5(e^2x)=7 | | 10x+23(x-5)=281 | | 6.5/39 | | (-6/-7)x(-5/3)x4 | | 3(x+7)-4x=12 | | -2(x+7)=6x-38 | | 6.2/0.05 | | (2/-5)(8)(-9/3) | | 5[1/2-x]=5/4 | | 9=0.2x*0.2x*0.6x | | 9=0.2x*0.2x*0.06x | | 8h-4h+2=78 | | 1-7x=7x-1 | | 7x+2=12.5 | | X^2+X-110+2(4)=8 | | 16/2=n | | 2(9x+5)=190 | | x^2-15x-44=7x+4 | | x^2+x-38=9x-5 | | 5x+2=x+3.6 | | x^2+11x+31=1 | | 5x=8y+1 | | -7x-1.6=-5-1.2 | | 8m-0=16 | | 4(6x-9)=180 |

Equations solver categories